Collaboration and technology : 23rd International Conference, CRIWG 2017, Saskatoon, SK, Canada, August 9-11, 2017, Proceedings /: 23rd International Conference, CRIWG 2017, Saskatoon, SK, Canada, August 9-11, 2017, Proceedings. (2017) - Unknown
No abstract available